Localización óptima de paraderos y diseño de rutas para el transporte del personal de trabajo de una empresa ubicada en la vía a Daule - Sánchez, Arturo (2010)
This paper presents the approach and solution to the problem of the location of bus stops and transfer of staff working at a company located on the outskirts of the city of Guayaquil, which has been divided into two stages. In the first stage is proposed integer programming model for locating the whereabouts using a very important tool as it is Gams, followed by the design of routes in the second stage by means of a heuristic and then improve the solutions found by an exchange algorithm, and all this through another software program (Mathematica).These algorithms provide effective solutions in the design of routes to visit daily for a homogeneous fleet of buses.